PENGARUH KEPEMIMPINAN, KOMUNIKASI INTERPERSONAL DAN PENEMPATAN PEGAWAI TERHADAP PRESTASI KERJA PADA DIREKTORAT JENDERAL BINA MARGA – KEMENTERIAN PEKERJAAN UMUM & PERUMAHAN RAKYAT (Ruang Lingkup PJN Wilayah I Sumatera Selatan) - Ratna Sari (Jurnal Manajemen, 2020)
The purpose of this study was to determine the effect of leadership, interpersonal communication and employee placement on achievement. The research method used is the correlation research method with a descriptive approach. The sampling technique was saturated sampling technique where the sample was the entire population. The analytical method used quantitative analysis with regression analysis methods, validity, reliability, multiple linear regression analysis, correlation analysis, coefficient of determination and hypothesis testing. The collected data were analyzed using multiple regression including t-test for partial test and F-test for simultaneous test. The results of the research simultaneously show that leadership, interpersonal communication, and employee placement have a positive and significant effect on job performance. Work at the Directorate General of Highways - Ministry of Public Works & Public Housing (Scope of BBPJN V - PJN Region I Sumsel).